2007
DOI: 10.5194/acp-7-661-2007
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of PM<sub>10</sub> main constituents in two valleys of the French Alps. I: EC/OC fractions

Abstract: Abstract. Daily PM 10 samples were collected at two urban sites within two valleys in the French Alps (Chamonix and St Jean de Maurienne) during a period of two and a half years. The carbonaceous species EC (elemental carbon) and OC (organic carbon) were analysed to investigate the possible sources of EC and OC, and their seasonal variations. Mean OC concentrations are in the very high range of concentrations measured for other European sites, and represent at least one third of the PM 10 mass on each site. On… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…Assuming that the functional groups fingerprints of the three sources described in this study are representative of the emissions and aerosol formation processes in the Chamonix valley, and that no heterogeneous chemical process has significantly modified the composition of the organic fraction during the aerosol atmospheric residence time, a large contribution of wood burning to the ambient OA can be assessed. This is in agreement with the wide use of wood combustion in the valley and with previous results obtained in the same location (Marchand et al, 2004;Jaffrezo et al, 2005;Aymoz et al, 2007). The predominance of the wood combustion contribution in such environments is also in good agreement with the source apportionment studies performed in similar alpine valleys during winter by Favez et al (2010) and by Sandradewi et al (2008), the latter attributing 88% of OA to wood burning emissions.…”
Section: Sources Discrimination Using Functional Group Fingerprintssupporting
confidence: 81%
“…Assuming that the functional groups fingerprints of the three sources described in this study are representative of the emissions and aerosol formation processes in the Chamonix valley, and that no heterogeneous chemical process has significantly modified the composition of the organic fraction during the aerosol atmospheric residence time, a large contribution of wood burning to the ambient OA can be assessed. This is in agreement with the wide use of wood combustion in the valley and with previous results obtained in the same location (Marchand et al, 2004;Jaffrezo et al, 2005;Aymoz et al, 2007). The predominance of the wood combustion contribution in such environments is also in good agreement with the source apportionment studies performed in similar alpine valleys during winter by Favez et al (2010) and by Sandradewi et al (2008), the latter attributing 88% of OA to wood burning emissions.…”
Section: Sources Discrimination Using Functional Group Fingerprintssupporting
confidence: 81%
“…Thus, the explanation for such a depletion measured for primary sea salt emissions can be either that a fractionation of chloride relative to sodium happens in the course of the aerosol emission due to a different composition of the sea surface microlayer, or that there is already a chloride volatilization process that takes place during the evaporation of the film drops to aerosol residuals. In the literature, chloride-to-sodium ratios measured in the aerosol phase in ambient marine environments have usually been found to be lower than 1.2 (Bardouki et al, 2003;Koulouri et al, 2008;Pey et al, 2013), with the chloride loss usually attributed to a loss in the form of HCl after sodium chloride has reacted with acidic gases such as HNO 3 or H 2 SO 4 during the "aging" process. Our results would call into question past conclusions about sea salt aging during transport in polluted air masses.…”
Section: Number and Ccn Concentrationsmentioning
confidence: 99%
“…The quartz fibre filters were immediately stored in a refrigerator after sampling and were later extracted with Milli-Q water and analysed by ion chromatography (IC) for anions (Cl − , NO (Jaffrezo et al, 1998). Analyses for elemental carbon (EC) and organic carbon (OC) were also performed using the thermo-optical transmission (TOT) method on a Sunset Lab analyser (Aymoz et al, 2007) following the EUSAAR2 temperature program proposed in Cavalli et al (2010). The aerosol flow from the other tank was passed through a diffusion drier and a soft X-ray aerosol neutralizer (TSI Model 3088) before entering a differential mobility particle analyzer (DMA).…”
Section: Sea Spray Generation and Characterizationmentioning
confidence: 99%
“…The carbonaceous content of HiVol and LPI samples were analyzed for EC and OC using a Thermo-Optical Transmission (TOT) method on a Sunset Lab analyzer (Birch and Cary, 1996;Aymoz et al, 2007). We used the recently developed EUSAAR2 temperature program proposed by Cavalli et al (2010).…”
Section: Off-line Chemical Analysesmentioning
confidence: 99%
“…For Europe, Puxbaum et al (2007) reported high contributions of biomass burning aerosols to the organic aerosol fraction during the winter season at various remote sites, which could be mainly attributed to residential wood burning. Significant wood burning emissions were moreover observed in Scandinavian rural sites, in Alpine valleys, as well as in central Europe rural sites (Ricard et al, 2002;Aymoz et al, 2007;Szidat et al, 2007;Sandradewi et al, 2008a;Caseiro et al, 2009;Lanz et al, 2009). For urban environments, Zdráhal et al (2002) estimated that wood burning emissions accounted for ∼35% of organic carbon (OC) in Ghent, Belgium, during a winter episode.…”
Section: Introductionmentioning
confidence: 99%